Matematyka
xonix
2021-04-08 10:08:17
Zapisz w postaci sumy algebraicznej: a) (2a+b)*c - ( 2ac-bc+1) = b) 2x^2(x-5) - 3x(x^2-3x+5) = c) 5(x-z) +2(z-x) =
Odpowiedź
Gosiaaa92
2021-04-08 11:58:22

a) (2a+b)*c - ( 2ac-bc+1) = 2ac+bc-2ac+bc-1=-1 b) 2x^2(x-5) - 3x(x^2-3x+5) =2x^3+10x^3-2x^2+9x^2-15x=12x^3+7x^2-15x c) 5(x-z) +2(z-x) =5x-5z+2z-2x=3x-3z

bezprzemocy
2021-04-08 11:59:37

[latex]a)=2ac+bc-2ac+bc-1=2bc+1\b)=2x^3-10x^2-3x^3+9x^2-15=-x^3-x^2-15=-(x^3+x^2+15)\c)=5x-5z+2z-2x=3x-3z[/latex]

Dodaj swoją odpowiedź